How Does Social Mobilization Shape the Collective Coproduction of Urban Community Regeneration in China? - Jinpeng Wu; Yuting Chen; Ruiqi Shi; Jing Xiong (Land)
Citizen participation has become a key part of promoting community regeneration and improving community governance. Coproduction, especially collective coproduction—a way in which residents can be deeply involved in community regeneration—is important to public service performance and social values. However, little research has empirically examined the patterns and determinants of collective coproduction. Against the backdrop of Chinese grassroots governance, this article employs social mobilization theory to explore the key factors contributing to collective coproduction and develops a theoretical framework that focuses on how the combination of top-down and bottom-up social mobilization shapes it. By comparing four urban cases of community regeneration coproduction in the P district of Shanghai, we conclude that when local governments perceive differentiated variations among governance objectives, they tend to come up with various social mobilization schemes accordingly. When local governments adopt all-around, point-to-point, targeted, or random mobilization schemes, this often results in four corresponding patterns of community collective coproduction: comprehensive, generalized, club, and formalistic. The contribution of this paper is in its provision of a comprehensive and dynamic viewpoint to explore the impact of social mobilization on community-based collective coproduction patterns, forming a new understanding of the collective coproduction formation mechanism.